Using multi-criteria decision-making for selecting a smart metering infrastructure - Echeverri Martinez, Ricardo Andres; Osorio Gómez, Juan Carlos; Echeverry Ibarra, Diego Fernando; Lozano Moncada, Carlos Arturo (Scientia et Technica, 2018)
In this research a methodology based on multi-criteriadecision analysis for the evaluation and selection ofinfrastructure energy smart metering in the Colombian contextis presented. The selection process of these measurementinfrastructures covers additional technical and financial criteria,becoming a complex problem. The methodology used in thiswork is the technique called Analytic Hierarchy Process (AHP)that considers seven assessment criteria (Technology, Finance,Environmental, Regulatory, Political, Infrastructure and SocioCultural).Of these assessment criteria, emerge 25 sub-criteria,which are integrated in a hierarchical structure to evaluate threeenergy smart metering alternatives. Nine experts were consultedto obtain the results. The results show the versatility of AHPmethod for making complex decisions with respect to theimplementation of energy smart metering infrastructure, andprovide a useful guide for assessing Smart Grid projects throughmulti-criteria analysis